THE PREDICTION OF INTERMODAL CONTAINER TRAFFIC OPERATOR WITH USING THE THEORY OF FUZZY SETS - Shvets, O. V. (Science and Transport Progress, 2009)
The task of this article is to make a forecast of the container flow (which is being mastered by intermodal transport operator) in order to determine in future such moment when the purchase of new transport unit will be most cost-effective. Here the analysis of existing forecast methods and appropriate software products is done as well as the own methods for forecasting the containers flow of intermodal transport operator which use fuzzy sets theory and methods of non-linear programming are offered.